Pesan Dakwah dalam Media Sosial (Analisis Semiotika terhadap Akun Youtube Ustadz Abdul Somad Official): Analisis Semiotika terhadap Akun Youtube Ustadz Abdul Somad Official - Nurhidayah; Umi Halwati; Nawawi (IQTIDA : Journal of Da'wah and Communication, 2023)
This research was conducted to find out the meaning of denotation, connotation, and myths of da'wah messages about the three great sins on Ustadz Abdul Somad's Official Youtube account. The part studied is the contents of Ustadz Abdul Somad Official's YouTube da'wah content. The data was taken from content entitled "3 Great Sins" during the recitation after dawn at the Sultan Mahmud Badaruddin Mosque on the link https://www.youtube.com/watch?v=qLHIBaIVSuQ which was uploaded on May 1, 2021 from Ustadz Abdul Somad's Official Youtube account . This research is a qualitative research model of Roland Barthes's semiotic analysis. The purpose of this research is to see how the contents of da'wah messages on Ustadz Abdul Somad Official's Youtube account, especially content with a discussion of the three great sins. The results of the study, there is a discussion that is included as a grave sin, namely, associating partners with Allah, disobedience to parents, and false witnesses.